Pain Distraction During Awake Major Colorectal Surgery: Supporting Patients Beyond the COVID-19 Era. Preliminary Findings - Romanzi, Andrea; Gallo, Gaetano; De Rango, Sabrina; Vignati, Barbara; Vannelli, Alberto (Frontiers in Surgery, 2021)
Introduction: During the coronavirus disease 2019 (COVID-19) pandemic, minimally invasive surgery and general anaesthesia (both aerosol-generating procedures) became controversial. We report a preliminary experience of awake undelayable colorectal surgeries which, innovatively, took advantage of intraoperative pain distraction. Moreover, we describe our frugal solution to social distancing in psychological support of inpatients. Methods: During the current pandemic, five patients underwent acute-care colorectal surgery under locoregional anaesthesia at our Department. Intraoperatively, a 3D mobile theatre (3DMT) was used to distract the patients from pain. Vital signs, pain intensity, ergonomic comfort/discomfort, sense of presence and distress were intraoperatively monitored. A postoperative “cuddle delivery” service was instituted: video messages from relatives and close friends were delivered daily to the patient through the 3DMT. Emotional effects were investigated through clinical interviews. Results: Both intraoperative and postoperative pain were always well controlled. Conversion to general anaesthesia and postoperative intensive support/monitoring were never necessary. The “cuddle delivery” initiative helped patients fill the emotional gap created by the strict containment measures implemented inside the hospital, distracting them from emotional anxiety and physical pain. Conclusions: During the next phases of the COVID-19 pandemic and even after the COVID-19 era, awake laparotomy under locoregional anaesthesia may be a crucial option for delivering acute-care surgery to selected patients when intensive care beds are unavailable and postponing surgery is unacceptable. We also introduce a new modality for the provision of emotional support during postoperative inpatient care as a countermeasure to the restrictions imposed by social distancing measures.